Pengaruh Penggunaan Smartphone terhadap Perilaku Remaja - Usman Usman; Yulida Maran (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Cell phones have become one of the requirements for the wider community. Today all people in the world can be connected by a modern communication tool that is supported by the development of sophisticated media and modern communication. One of the media such as the mobile phone is now better known as "smart phones". The rise of smart phone usage among teens sparked a wide range of issues related to individual behavior and social behavior of adolescents themselves. This study used a qualitative approach with descriptive type. The technique of collecting data was taken with a total sampling was 28 people. The data collection techniques used was observation, interviews and focus group discussion. Data were analyzed through several stages: among other subjects through testing credibility, authenticity, triangulation analysis, and intersubjectivity analysis. From the research that has been conducted showed that the use of smart phones in adolescents can meet their needs. Fulfillment of requirements obtained from the use of smart phones in the range of cognitive needs, affective needs, personal integrative needs and requirements as well as the social integrative needs to release tension. Fulfillment of various needs in the above cause a variety of effects, both positive and negative.